EXPANDING THE TYPES OF FINANCIAL SERVICES OFFERED BY COMMERCIAL BANKS IN THE NEW UZBEKISTAN (World Economics and Finance Bulletin, 2023)
The research examines the types of financial services provided by private and state-owned banks, as well as problems and current proposals for further improvement of activities through the introduction of new financial services in private banks in the Republic of Uzbekistan
Keywords: Bank; banking regulations; financial services